Experimental research and simulation verification of recycling process of heat transfer oil. (14th June 2022) - Liu, Guorong
Heat transfer oil will inevitably deteriorate after long time use, leading to the gradual accumulation of material insoluble in acetone in hot medium oil that seriously exceeds the standard. Therefore, extending the service life of heat transfer oil is an important means to improve economic benefits. In this experiment, solvent extraction settlement method was used to remove material insoluble in acetone. By designing a set of extractive settlers, sedimentation experiments were carried out with different solvents, moreover, the acetone-insoluble content, kinematic viscosity and neutralisation value of the extracted heat transfer oil were detected. Computational fluid dynamics was used to verify the effect of asphalt settlement separation tank by numerical simulation. The experiments were validated by measuring the extraction effects of different solvents. The results have important implications for industrial production.